On the tectonic history and some related sedimentational aspects of the Witwatersrand and Ventersdorp systems in the Far East Rand during upper-Witwatersrand, pre-Transvaal system time - Cluver, A. F.(Albert Frederick) (Stellenbosch : Stellenbosch University, 2012)
Maps in back pocket of book.